LEGAL PROTECTION OF NOTARIES IN DISPUTES OVER DEFAULT OF SALE-PURCHASE AGREEMENTS - Ulina Manurung, Hot; Sri Marniati, Felicitas; Suasungnern, Sineerat (Penerbit Lafadz Jaya, 2024)
This research aims to review and analyse the legal protection provided to notaries in disputes over default of land sale and purchase agreement (PPJB) in Indonesia. The main focus of this research is to identify the extent to which existing legal provisions, both in Law Number 2 Year 2014 on the Notary Position (UUJN) and in the Criminal Code (KUHP), can protect notaries from the legal consequences that may arise in cases of default. Through a normative legal approach, this study finds that although UUJN authorises notaries to draft valid authentic deeds, legal protection for notaries in the context of default disputes is still limited. Therefore, this study recommends the strengthening of more comprehensive regulations and clearer legal protection mechanisms for notaries, in order to provide legal certainty in carrying out their professional duties. This research is expected to contribute to the understanding of the rights and obligations of notaries and strengthen the integrity of the land law system in Indonesia.